Understanding industry 4.0 : AI, the Internet of things, and the future of work - Sergi, Bruno S.; Popkova, Elena G.; Bogoviz, Aleksei V.; Litvinova, Tatiana N. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Everywhere you look, there are signs of the Fourth Industrial Revolution. R&D on leading digital technologies is conducted around the world, exploring novel technologies aimed at cyber-physical systems, such as the Internet of Things (IoT), Blockchain, 3D Printing, Virtual Reality, AI, and many more. With these rapid changes in technology comes social evolution and the potential for future social crises. Understanding Industry 4.0: AI, the Internet of Things, and the Future of Work looks to determine the most probable oncoming changes in key areas of the economy, to highlight the most important professions of the future, and to offer recommendations for their correct selection and successful mastering. Including sections on careers in education, medicine, R&D, and agriculture, among others, economics experts Bruno S. Sergi, Elena G. Popkova, Aleksei V. Bogoviz, and Tatiana N. Litvinova explore the vastly changing modern workplace and offer a guide to navigating through and adapting to this evolution. For researchers and students of management, economics, and business, this is an unmissable exploration of the new frontier of Industry 4.0.
Includes bibliographical references and index.
Keywords: Appropriate technology; Technological innovations; Technology and state; Business & Economics -- Development -- Business Development; Business innovation